Stimulasi Kreativitas Anak Melalui Kegiatan Menghias Roti Tawar di Taman Kanak-kanak - Isra Yenti; Saridewi Saridewi (RC-INSTITUT, 2020)
The objective of this study is to describe children's creativity through decorating bread. The writer used a descriptive qualitative research method with a literature study from various written sources such as articles, journals, and documents that are relevant to the research. Based on the results of a review of several study journals, decorating activities using bread can stimulate children's creativity. It is concluded that the activity of decorating bread can stimulate children's creativity.